(untitled) (Hekima Review, 2005)
When I showed my copy of Tanner’s The Mass to a learned friend, his immediate reaction was, “Rather than speaking about ‘problems’, these days people prefer to talk about ‘challenges.’” The word ‘problem’ appears in twelve out of his fifteen chapter titles. For someone who has read the book, this usage is a matter of choice, not an oversight. Tanner manifests a rare courage by pointing out problematic details which tend to be overlooked in our cross-cultural globalized celebration of “probably the commonest contemporary religious ritual on a par with the Muslim prayer ritual” (1).